Islamic Political Thought: Relevance of Classical Ideals in Contemporary Governance - Muhammad Atta Ullah; Muhammad Ubaid Ullah; Muhammad Inayat Ullah (Journal of Religion and Society, 2025)
The paper, "Islamic Political Thought: Relevance of Classical Ideals in Contemporary Governance," explores the enduring influence of classical Islamic political theories in modern governance. It emphasizes the crucial role of historical Islamic principles in addressing current socio-political challenges. Key themes include the ethical frameworks of governance and the application of concepts like 'Maslaha' (public interest), emphasizing justice, accountability, and the common good as foundational for ethical governance. The paper also discusses the dynamic nature of Islamic political thought, characterized by its adaptability and relevance across different historical and contemporary contexts. It delves into the roles of key figures such as al-Farabi and Ibn Khaldun, highlighting their contributions to political thought and the concept of social cohesion and unity as essential for political power. Furthermore, the document critically analyzes how classical principles can inform current debates on governance, suggesting that insights from Islamic political thought can foster enhanced governance frameworks in Muslim societies. It calls for a nuanced appreciation of these ideals to navigate modern governance complexities effectively. Keywords: Islamic Political Thought, Classical Ideals, Contemporary Governance, Ethical Frameworks, Maslaha, Social Cohesion, Justice, Accountability